Metal-organic framework material for adsorbing iodine ions, preparation method and application thereof

CN123003897APending Publication Date: 2026-10-30CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611447837.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-17
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但在实际应用中,含碘工业废水中通常伴随着大量的氯离子和溴离子,这些卤素离子的性质相似,容易形成竞争吸附,难以实现从较低碘浓度的废水中选择性富集碘离子

Benefits of technology

本发明采用静电吸引、疏水基团、孔道设计的协同作用,制备一种具有高选择性的金属-有机框架材料。碘离子的电子层数相较于溴离子和氯离子更多,因此极化率较高,更容易被静电吸引,基于金属与有机配体之间的配位作用,选用含氨基的有机配体,合成含有氨基的金属有机框架粉末,采用后修饰的方法,加入卤代烃与金属有机框架粉末中的氨基进行季铵功能化反应,引入阳离子,对极化率较高的碘离子提供静电吸引力。碘离子的水合能相较于溴离子和氯离子更低,更容易脱水合,因此,在上述材料的基础上,通过原位生长的方式,在季铵功能化的金属有机框架粉末表面生长一层具有直径为2.5-3.3 Å孔道、具有含氟配体的金属有机框架,可以诱导碘离子在经典吸引力的作用下优先接触疏水基团,发生脱水合作用,进入预先设计的孔径,大大提高碘离子对氯离子和溴离子的分离效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003897A_ABST
    Figure CN123003897A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of organic framework functional materials, and particularly relates to a metal-organic framework material for adsorbing iodine ions, a preparation method and application. The metal-organic framework material with high selectivity is prepared by the synergistic effect of electrostatic attraction, hydrophobic groups and channel design. Based on the coordination between the metal and the organic ligand, the organic ligand containing amino groups is selected, the metal-organic framework powder containing amino groups is synthesized, the halogenated hydrocarbon is added to the amino groups in the metal-organic framework powder by the post-modification method, the quaternary ammonium functionalization reaction is carried out, the cation is introduced, the electrostatic attraction force is provided for the iodine ions with high polarizability, the fluorine-containing hydrophobic groups are grown in situ on the surface of the material, the iodine ions are induced to preferentially contact the hydrophobic groups under the action of the classical attraction force, the dehydration reaction occurs, and thus the separation efficiency of the iodine ions to the chlorine ions and the bromine ions is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic framework functional materials technology, specifically relating to a metal-organic framework material that adsorbs iodine ions, its preparation method, and its application. Background Technology

[0002] Iodine is extremely scarce in the Earth's crust, belonging to the typical rare and dispersed elements. Iodine compounds play an irreplaceable role in food additives, medical contrast agents, polarizing films for liquid crystal displays, and high-purity semiconductor materials. For a considerable period, efficiently recovering iodine from various iodine-containing resources is the most effective and reliable way to address iodine scarcity. Among many iodine-containing wastes, zinc oxide slag is a secondary iodine resource with significant development value. Zinc oxide slag mainly originates from dust generated during iron and steel smelting and slag produced during non-ferrous metal smelting. In these metallurgical processes, trace amounts of iodine associated with the raw materials volatilize into the dust collection system and eventually accumulate in the zinc oxide slag, forming a solid-phase iodine resource with an iodine content typically ranging from hundreds to thousands of ppm. This iodine usually exists in ionic form and can enter wastewater after water or alkali washing. The main impurity anions are bromide and chloride ions.

[0003] Adsorption is an effective strategy for enriching iodide ions in wastewater. Porous materials such as porous organic polymers, metal-organic frameworks, and covalent-organic frameworks have been studied as highly efficient adsorbents for capturing iodide ions due to their high specific surface area and customizable adsorption sites. Existing metal-organic framework materials enhance their adsorption capacity for iodide ions by adding functional groups (amino, hydroxyl) and silver ions during preparation. However, in practical applications, iodine-containing industrial wastewater is usually accompanied by large amounts of chloride and bromide ions. These halide ions have similar properties and easily form competitive adsorption, making it difficult to selectively enrich iodide ions from wastewater with low iodine concentrations. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a metal-organic framework material for adsorbing iodine ions, its preparation method, and its application.

[0005] A method for preparing a metal-organic framework material that selectively adsorbs iodine ions includes the following steps: A metal-organic framework containing amino groups is dispersed in an organic solvent, a haloalkane is added, and a quaternary ammonium reaction occurs under a nitrogen atmosphere to obtain a quaternary ammonium-functionalized metal-organic framework. A quaternary ammonium-functionalized metal-organic framework was dispersed in a mixed solution of water and ethanol. A fluorine-containing organic ligand powder and the metal salt were added, followed by the addition of glacial acetic acid. The mixture was heated at 75°C to 85°C for 70 to 75 hours, and the product was collected by filtration to obtain the metal-organic framework material. The molar ratio of the fluorine-containing organic ligand to the metal salt was 1:0.2 to 3, and the ratio of the quaternary ammonium-functionalized metal-organic framework to the fluorine-containing organic ligand was 1 g:0.8 mmol to 1.2 mmol.

[0006] This invention synthesizes an amino-containing metal-organic framework powder by coordinating an amino-containing organic ligand with a metal center, and then performs a quaternary ammonium functionalization reaction on the amino group to introduce a cation, which provides electrostatic attraction to iodide ions with high polarizability. Fluorohydrophobic groups grown in situ on the surface of the material, with pores of 2.5-3.3 Å, induce iodide ions to preferentially contact the hydrophobic groups under the action of classical attraction, and undergo dehydration, thereby improving the separation efficiency of iodide ions for chloride and bromide ions.

[0007] Preferably, the preparation steps of the amino-containing metal-organic framework are as follows: dissolve the amino-containing organic ligand powder and metal salt in DMF, add glacial acetic acid, heat at 75℃~100℃ for 70h~75h, filter and collect the product to obtain the amino-containing metal-organic framework; the molar ratio of the organic ligand and the metal salt is 1:0.2~3.

[0008] Preferably, the organic ligand containing an amino group is 2-aminoterephthalic acid, 2,5-diaminoterephthalic acid, 2-amino-1,3,5-benzenetricarboxylic acid, 2-aminobenzimidazole, 4-aminopyrazole or 3-aminopyrazole.

[0009] Preferably, the metal salt is zirconium chloride, hafnium chloride, copper sulfate, copper nitrate trihydrate, aluminum chloride hexahydrate, anhydrous aluminum chloride, aluminum sulfate octadecahydrate, aluminum sulfate hydrate, aluminum sulfate, aluminum nitrate nonahydrate, aluminum nitrate hydrate, zinc nitrate hydrate, or zinc nitrate hexahydrate.

[0010] Preferably, the fluorinated organic ligand is tetrafluoroterephthalic acid, 2,5-bis(trifluoromethyl)terephthalic acid, 2-fluoro-1,3,5-benzenetricarboxylic acid, 2-(trifluoromethyl)-1H-imidazolium, 2-methyl-4-trifluoromethylimidazolium, or 4-fluoro-1H-pyrazole.

[0011] Preferably, the organic solvent is methanol, acetonitrile, or acetone.

[0012] Preferably, the haloalkane is iodomethane, iodoethane, bromomethane, or bromoethane, and the final concentration of the haloalkane is 0.01 mol / L to 10 mol / L.

[0013] The metal-organic framework material prepared by the aforementioned preparation method.

[0014] Preferably, the size of the metal-organic framework powder material is 50 nm to 2 μm.

[0015] The application of the metal-organic framework material in iodine recovery, wherein the iodine is derived from zinc oxide slag.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention utilizes the synergistic effect of electrostatic attraction, hydrophobic groups, and pore design to prepare a highly selective metal-organic framework (MOF) material. Iodide ions have more electron shells than bromide and chloride ions, resulting in higher polarizability and easier electrostatic attraction. Based on the coordination interaction between metal and organic ligands, amino-containing organic ligands are selected to synthesize amino-containing MOF powders. A post-modification method is used to add haloalkanes to the amino groups in the MOF powder for quaternary ammonium functionalization, introducing cations that provide electrostatic attraction to the highly polarizable iodide ions. Iodide ions have a lower hydration energy than bromide and chloride ions, making them more prone to dehydration. Therefore, based on the above material, an in-situ growth layer with fluorine-containing ligands and pores of 2.5-3.3 Å diameter is grown on the surface of the quaternary ammonium functionalized MOF powder. This induces iodide ions to preferentially contact hydrophobic groups under classical attraction, undergoing dehydration and entering the pre-designed pores, significantly improving the separation efficiency of iodide ions for chloride and bromide ions. Attached Figure Description

[0017] Figure 1 The image shows the SEM image of the metal-organic framework material provided in Example 1 of this invention.

[0018] Figure 2 The image shows the SEM image of the metal-organic framework material provided in Example 2 of this invention.

[0019] Figure 3 The graph shows a comparison of the separation efficiency of metal-organic framework materials provided in the embodiments and comparative examples of the present invention. Detailed Implementation

[0020] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. Unless otherwise specified, the experimental methods described in the embodiments of the present invention are conventional methods.

[0021] Example 1 Preparation of copper-based pyromellitic acid-fluorinated-quaternized metal-organic framework materials: S1. Take 3 mmol of 2-amino-1,3,5-benzenetricarboxylic acid and 2 mmol of copper nitrate trihydrate, dissolve them in 10 ml of DMF, and slowly add 2 ml of glacial acetic acid. The final concentration of glacial acetic acid is 0.01~10 mol / L. In this example, the final concentration of glacial acetic acid is 0.1 mol / L. Place the mixture in an oven and heat it at 80°C for 72 hours. Filter the product, wash it with water and alcohol, dry it, and activate it under vacuum at 60°C for 24 hours to obtain a copper-based metal-organic framework powder containing amino groups.

[0022] S2. Disperse 1g of amino-containing copper-based metal-organic framework powder in 20ml of acetone, add 1ml of iodomethane to make the concentration of iodomethane 0.1mol / L, heat at 80℃ for 72 hours under nitrogen atmosphere, collect the product, wash with water, wash with alcohol, dry and activate under vacuum at 60℃ for 24 hours to obtain quaternary ammonium functionalized copper-based metal-organic framework.

[0023] S3. 1 g of quaternary ammonium-functionalized copper-based metal-organic framework was dispersed in a mixed solution of 10 ml of water and ethanol at a water-to-ethanol ratio of 8:1. 0.9 mmol of 2-fluoro-1,3,5-benzenetricarboxylic acid and 0.6 mmol of copper nitrate trihydrate were added, and 1 ml of glacial acetic acid was slowly added. The mixture was placed in an oven and heated at 80 °C for 72 hours. The product was collected, washed with water and alcohol, dried, and then activated under vacuum at 60 °C for 24 hours. A layer of fluorinated hydrophobic groups with specific pore sizes was grown on the surface of the quaternary ammonium-functionalized metal-organic framework to obtain a copper-based pyromellitic acid-fluorinated-quaternized metal-organic framework material.

[0024] The morphology of the obtained copper-based pyromellitic acid-fluorinated quaternized metal-organic framework material was observed using scanning electron microscopy (SEM). The obtained SEM images are shown below. Figure 1 As shown in the figure, the copper-based pyromellitic acid-fluorinated quaternized metal-organic framework material consists of uniform 100nm crystal particles.

[0025] Example 2 Preparation of zirconium-based terephthalic acid-fluorinated quaternized metal-organic framework materials: S1. Take 3 mmol of 2-aminoterephthalic acid and 2 mmol of zirconium chloride, dissolve them in 15 ml of DMF, slowly add 2 ml of glacial acetic acid, place in an oven and heat at 100 °C for 72 hours, filter the product, wash with water, wash with alcohol, dry and activate under vacuum to obtain zirconium-based metal-organic framework powder containing amino groups. S2. Disperse 1g of amino-containing zirconium-based metal-organic framework powder in 20ml of acetone, add 1ml of iodomethane to make the concentration of iodomethane 0.1mol / L, heat and react under nitrogen atmosphere for 72 hours, collect the product, wash with water, wash with alcohol, dry and activate under vacuum to obtain quaternary ammonium functionalized zirconium-based metal-organic framework.

[0026] S3. 1 g of quaternary ammonium-functionalized zirconium-based metal-organic framework was dispersed in a mixed solution of 10 ml of water and ethanol at a water-to-ethanol ratio of 8:1. 0.9 mmol of 2,5-bis(trifluoromethyl)terephthalic acid and 0.6 mmol of zirconium chloride were added, followed by the slow addition of 1 ml of glacial acetic acid. The mixture was placed in an oven and heated at 100 °C for 72 hours. The product was collected, washed with water and alcohol, dried, and activated under vacuum to obtain a zirconium-based terephthalic acid-fluorinated-quaternized metal-organic framework material.

[0027] The morphology of the obtained zirconium-based terephthalic acid-fluorinated quaternary ammonium metal-organic framework was observed using SEM, and the resulting SEM images are shown below. Figure 2 As shown in the figure, the zirconium-based terephthalic acid-fluorine-quaternized metal-organic framework material consists of uniform 200nm crystal particles.

[0028] Example 3 The difference between Example 3 and Example 1 is that the molar amount of copper nitrate trihydrate in S1 is 8 mmol, and the molar amount of copper nitrate trihydrate in S3 is 2 mmol. All other conditions and steps are the same as in Example 1.

[0029] Example 4 The difference between Example 4 and Example 1 is that the molar amount of copper nitrate trihydrate in S1 is 1 mmol, and the molar amount of copper nitrate trihydrate in S3 is 0.2 mmol. All other conditions and steps are the same as in Example 1.

[0030] Comparative Example 1 Preparation of zirconium-based terephthalic acid-fluorine metal-organic framework materials: Unlike Example 2, step S2 is omitted, while the other steps and conditions are the same as in Example 2.

[0031] Comparative Example 2 Preparation of zirconium-based terephthalic acid-quaternized metal-organic framework materials: Unlike Example 2, step S3 is omitted, while the other steps and conditions are the same as in Example 2.

[0032] Performance testing The iodine adsorption and selective separation properties of the metal-organic framework materials prepared in Examples 1, 2, 1, and 2 were tested in zinc oxide slag leachate.

[0033] 100 mg of the metal-organic framework materials prepared in Examples 1, 2, Comparative Examples 1, and 2 were respectively placed in 100 ml of zinc oxide slag leachate. After soaking and adsorption at 25 °C for 2 h, the filtrates were collected by filtration, yielding filtrate 1, filtrate 2, filtrate 3, and filtrate 4, which were designated as Sample 1, Sample 2, Sample 3, and Sample 4, respectively. Ion chromatography was used to test the I content in the zinc oxide slag leachate, Sample 1, Sample 2, Sample 3, and Sample 4. - Cl - ,Br - The concentration.

[0034] The I in the leachate before and after adsorption was calculated. - / Cl - and I - / Br - Calculate I - / Cl - and I - / Br - The separation coefficient, such as Figure 3 As shown, the material I obtained in Example 1 - / Cl - and I - / Br - The separation coefficients were 409 and 312, respectively, and the I of the material obtained in Example 2 - / Cl - and I - / Br - The separation coefficients were 489 and 392, respectively, both materials exhibiting high separation coefficients. The material obtained in Comparative Example 1... - / Cl - and I - / Br - The separation coefficients were 71 and 23, respectively. This is because the materials did not undergo quaternary ammonium functionalization. - The lack of energy required for dehydration results in a low separation coefficient. The material obtained in Comparative Example 2 has an I... - / Cl - and I - / Br - The separation coefficients are 3 and 2, respectively. This is because the materials are not coated with fluorine-containing metal-organic frameworks. - The inability to dehydrate results in low separation.

[0035] It should be noted that when numerical ranges are mentioned in the claims of this invention, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. To avoid redundancy, the present invention describes preferred embodiments.

[0036] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.

[0037] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A method for preparing a metal-organic framework material that selectively adsorbs iodide ions, characterized in that, Includes the following steps: A metal-organic framework containing amino groups is dispersed in an organic solvent, a haloalkane is added, and a quaternary ammonium reaction occurs under a nitrogen atmosphere to obtain a quaternary ammonium-functionalized metal-organic framework. A quaternary ammonium-functionalized metal-organic framework was dispersed in a mixed solution of water and ethanol. A fluorine-containing organic ligand powder and the metal salt were added, followed by the addition of glacial acetic acid. The mixture was reacted at 75°C to 85°C for 70 to 75 hours, and the product was collected by filtration to obtain the metal-organic framework material. The molar ratio of the fluorine-containing organic ligand to the metal salt was 1:0.2 to 3, and the ratio of the quaternary ammonium-functionalized metal-organic framework to the fluorine-containing organic ligand was 1 g:0.8 mmol to 1.2 mmol.

2. The preparation method according to claim 1, characterized in that, The preparation steps of the amino-containing metal-organic framework are as follows: dissolve the amino-containing organic ligand powder and metal salt in DMF, add glacial acetic acid, heat at 75℃~100℃ for 70h~75h, filter and collect the product to obtain the amino-containing metal-organic framework; the molar ratio of the organic ligand and the metal salt is 1:0.2~3.

3. The preparation method according to claim 2, characterized in that, The organic ligands containing amino groups are 2-aminoterephthalic acid, 2,5-diaminoterephthalic acid, 2-amino-1,3,5-benzenetricarboxylic acid, 2-aminobenzimidazole, 4-aminopyrazole, or 3-aminopyrazole.

4. The preparation method according to claim 2, characterized in that, The metal salt is zirconium chloride, hafnium chloride, copper sulfate, copper nitrate trihydrate, aluminum chloride hexahydrate, anhydrous aluminum chloride, aluminum sulfate octadecahydrate, aluminum sulfate hydrate, aluminum sulfate, aluminum nitrate nonahydrate, aluminum nitrate hydrate, zinc nitrate hydrate, or zinc nitrate hexahydrate.

5. The preparation method according to claim 1, characterized in that, The fluorinated organic ligand is tetrafluoroterephthalic acid, 2,5-bis(trifluoromethyl)terephthalic acid, 2-fluoro-1,3,5-benzenetricarboxylic acid, 2-(trifluoromethyl)-1H-imidazolium, 2-methyl-4-trifluoromethylimidazolium, or 4-fluoro-1H-pyrazole.

6. The preparation method according to claim 1, characterized in that, The organic solvent is methanol, acetonitrile, or acetone.

7. The preparation method according to claim 1, characterized in that, The halogenated hydrocarbon is iodomethane, iodoethane, bromomethane, or bromoethane, and the final concentration of the halogenated hydrocarbon is 0.01 mol / L to 10 mol / L.

8. The metal-organic framework material prepared by the preparation method according to any one of claims 1 to 7.

9. The metal-organic framework material according to claim 8, characterized in that, The metal-organic framework material has a size of 50 nm to 2 μm.

10. The application of the metal-organic framework material according to claim 8 in iodine recovery, characterized in that, The iodine comes from zinc oxide slag.